Fundusze strukturalne a małe i średnie przedsiębiorstwa w Polsce - Sieradzka, Katarzyna (Structural Funds and Their Absorption by the SMES Sector in Poland, 2007)
The paper discussed problem of EU structural funds absorption by the SMES sector in Poland. EU financial resources and operational programmes in particular Sectoral Operational Programme -Increased Enterprise Competitiveness have been characterized. In addition, absorption of European Union structural funds by the Polish SMES sector has been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 358-366